2023
DOI: 10.1101/2023.03.13.532061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ubiquitous, B12-dependent virioplankton utilizing ribonucleotide triphosphate reductase demonstrate interseasonal dynamics and associate with a diverse range of bacterial hosts in the pelagic ocean

Abstract: Through infection and lysis of their coexisting bacterial hosts, viruses impact the biogeochemical cycles sustaining globally significant pelagic oceanic ecosystems. Currently, little is known of the ecological interactions between lytic viruses and their bacterial hosts underlying these biogeochemical impacts at ecosystem scales. This study focused on populations of lytic viruses carrying the B12 dependent Class II monomeric ribonucleotide reductase (RNR) gene, ribonucleotide triphosphate reductase (RTPR), do… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…Despite the fact that there is no universal marker gene carried by all viruses, studies of specific hallmark genes have revealed large-scale viral diversity of certain viral groups from marine and host associated biomes [23][24][25][26][27][28] . For example, Sakowski et al 2014 and Wu et al 2023 found great novel dsDNA bacteriophage diversity from marine samples using ribonucleotide reductase 23,28 while Wolf et al 2020, Zayed et al 2022 andEdgar et al 2022 expanded the known RNA viruses using RNA-dependent RNA polymerase as a marker [25][26][27] . Complementary to marker gene approaches, shotgun metagenomic sequencing is suitable for discovering viruses without targeted marker genes 29,30 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that there is no universal marker gene carried by all viruses, studies of specific hallmark genes have revealed large-scale viral diversity of certain viral groups from marine and host associated biomes [23][24][25][26][27][28] . For example, Sakowski et al 2014 and Wu et al 2023 found great novel dsDNA bacteriophage diversity from marine samples using ribonucleotide reductase 23,28 while Wolf et al 2020, Zayed et al 2022 andEdgar et al 2022 expanded the known RNA viruses using RNA-dependent RNA polymerase as a marker [25][26][27] . Complementary to marker gene approaches, shotgun metagenomic sequencing is suitable for discovering viruses without targeted marker genes 29,30 .…”
Section: Introductionmentioning
confidence: 99%